The Big Bad Wolf sale is back again and their first stop is Pahang - Grace, Sundram (2020)
Known as the World’s Biggest Book Sale, the Big Bad Wolf Book Sale is returning to Pahang from 28 February to 9 March 2020 at Kompleks Sukan, Universiti Malaysia Pahang, Gambang Campus from 10 am to 12 midnight daily. Admission to the 11-day Book Sale is FREE and book lovers can enjoy books at 75% to 95% off recommended retail prices.